Pengembangan Media MACO (Math Comics) Berbasis Realistic Mathematics Education Pada Materi Program Linier - Sella ‘Izzata Awwaliya; Lady Agustina (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Universitas Pamulang, Indonesia, 2025)
The research was conducted to design and develop MaCo (Math Comics) learning media based on Realistic Mathematics Education (RME) which is expected to have the characteristics of validity, practicality, and effectiveness in improving learning outcomes and motivating students at the Senior High School (SMA) level. This research applies the ADDIE development model which consists of five main stages, namely Analysis, Design, Development, Implementation, and Evaluation. The results of material validation by material experts showed a percentage of 94% and 92%, while validation by media experts showed a percentage of 92% and 98% which were all included in the very valid category. After going through a revision process based on input from experts, the learning media developed was then tested on grade XI students at SMA Muhammadiyah 3 Jember to evaluate its effectiveness and practicality in supporting the learning process. Based on the results of the students' response questionnaire, a percentage of 86% was obtained which indicated that the learning media was included in the practical criteria. Furthermore, based on the comparison of pretest and posttest scores, an N-Gain value of 0.75 was obtained which was included in the criteria for high improvement in mathematics learning outcomes. While the N-Gain value for learning interest reached 0.55 which is included in the criteria for moderate improvement. Thus, it can be concluded that MaCo (Math Comics) media based on Realistic Mathematics Education (RME) is proven to meet the criteria of validity, practicality, and effectiveness, so it is feasible to be applied in the learning process to improve the quality and learning outcomes of students.